Ocular findings in children, adolescents and young adults with type 1 diabetes mellitus in ghana: a cross-sectional study - Serwah Bonsu Asafo-Agyei; Emmanuel Ameyaw; Amos Aikins (BMC Ophthalmology)
Abstract Background This study sought to determine the prevalence and types of ocular pathologies in Ghanaian children and young adults with type 1 diabetes mellitus (T1DM). Methods This cross-sectional study was conducted during a 4-day annual T1DM camp in December 2024. An ophthalmologic examination was performed, including visual acuity assessment, slit-lamp examination, and dilated fundoscopy. The visual acuity of participants with established refractive errors was evaluated after refractive correction. Visual impairment was classified as mild, moderate, or severe based on the International Classification of Diseases 11 definitions of visual impairment and blindness. Sociodemographics, HbA1c, and information about diabetes onset and duration were also documented. Univariate and multivariate analyses were used to evaluate for potential associations between ocular abnormalities and diabetes-related factors such as HbA1c, diabetes duration and patient age. Results A total of 110 children, adolescents and young adults (mean age 18.8 years, SD 5.0) were examined. The study cohort comprised 71 females (64.5%) and 39 males (35.5%). The mean duration of diabetes was 6.3 years (SD 3.9). The mean HbA1c was 10% (SD 1.8). No cases of diabetic retinopathy were observed. However, 43.6% of the participants had some degree of visual impairment. Other ocular findings, including iris atrophy (0.9%), cataracts (3.6%), intraocular lens posterior capsule opacification (1.8%) and a posterior chamber intraocular lens (0.9%), were also documented. Univariate analysis demonstrated a significant association between the duration of diabetes and the presence of right lens abnormalities. In multivariate analysis, increasing patient age emerged as an independent predictor of lens abnormalities. Additionally, higher HbA1c levels and longer duration of diabetes were positively correlated with the presence of visual impairment. Conclusion While no cases of diabetic retinopathy were detected in this population, a significant proportion of youth with T1DM had visual impairment and lens abnormalities. Clinical trial number Not applicable.